The post-ınstruction conceptions about conservation of mechanical energy: Findings from a survey research with high school and sniversity students: Research Article - Halilovic, Asila; Mešić, Vanes; Hasović , Elvedin; Vidak, Andrej (Journal of Turkish Science Education, 2022)
In this study, our aim was to identify high school and university students’ postinstruction conceptions about the law of conservation of mechanical energy (LCME). A cross-sectional survey design was used. Firstly, a test consisting of 14 multiple-choice questions was developed. 23 physics teachers analysed the test and concluded that our questions are useful for measuring understanding about the LCME. Next, the test was administered to a convenient sample of high school and university students who had already received conventional instruction about the energy concept. The sample consisted of 138 students from the University of Zagreb (Croatia), and 115 high school students from two different schools in Sarajevo (Bosnia and Herzegovina). While the distribution of item difficulties was good, the reliability of test scores proved to be barely acceptable. Therefore, we primarily focused on analysing how frequently the students chose the individual distractors and drew corresponding conclusions about students’ conceptions. It has been shown that many students associate conservation of mechanical energy with certain surface features of physical problems (e.g., “pulley problems”), instead of reasoning about the processes a chosen system undergoes over time. Students often believe that mechanical energy is conserved even for phenomena in which air resistance cannot be neglected. Similarly, they sometimes do not recognize that most collisions of everyday objects necessarily include the conversion of mechanical energy into thermal energy. We could conclude that many students from all educational levels in Bosnia and Herzegovina and Croatia still fail to apply a system-based approach to energy analysis.